EFEKTIVITAS JENIS PELARUT DAN LAMA EKSTRAKSI TERHADAP KARAKTERISTIK CONCRETE MINYAK ATSIRI KULIT JERUK MANDARIN (Citrus reticulata) - Putra Adiyasa, I Ketut Gede; Wrasiati, Ni Luh Putu; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aimed of this research were 1) to find out the effect of solvent type and extraction time on the characteristics of mandarin orange peel concrete, 2) to determine the solvent type and extraction time for producing the best characteristics of mandarin orange peel concrete and 3) to determine the compounds contained in the concrete of mandarin orange peel. This study used a factorial Randomized Block Design. The first factor was solvent type which consisted of 3 levels namely : nhexane, ethyl acetate and ethanol. The second factor was extraction time consisted of 3 levels namely : 3, 4, and 5 hours. Two groups of treatment were experimented, based on the time of experiment implementation. The results showed that the solvent type significantly affected the yield and characteristics of mandarin orange peel concrete, while extraction time and its interaction did not affect the variables observed. Using extraction solution of ethanol and extraction time for 5 hours was the best treatment to produce concrete of mandarin orange peel. The yield of the treatment was 47,65%, with the preference of flavor like to very like and strength of flavour was 3,90. By using GC-MS, the compounds contained in the concrete were identified as Naphthalene, 1,2,3,5,6, 8a-hexahydro-4, 7-dimethyl1-1-(1-metylethyl)-, (1S-cis); n-Hexadecanoic acid; Hexadecanoic acid, ethyl ester; 9,12-Octadecadienoic acid (Z, Z)-; Linoleic acid ethyl ester; D, .alpa. –Tocopherol and 4H-1-Benzopyran-4-one, 2-(3,4-dimethoxyphenyl)-5,6,7-trimethoxy.
Keywords: 69